2016
DOI: 10.1038/bjc.2016.107
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and toxicity of treatment with the anti-CTLA-4 antibody ipilimumab in patients with metastatic melanoma after prior anti-PD-1 therapy

Abstract: Background:Recent phase III clinical trials have established the superiority of the anti-PD-1 antibodies pembrolizumab and nivolumab over the anti-CTLA-4 antibody ipilimumab in the first-line treatment of patients with advanced melanoma. Ipilimumab will be considered for second-line treatment after the failure of anti-PD-1 therapy.Methods:We retrospectively identified a cohort of 40 patients with metastatic melanoma who received single-agent anti-PD-1 therapy with pembrolizumab or nivolumab and were treated on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(95 citation statements)
references
References 27 publications
2
91
1
1
Order By: Relevance
“…Developing second‐line therapies is key as the treatment options for these patients are ineffective. For example, melanoma patients treated with anti‐CTLA‐4 as a second‐line therapy for anti‐PD‐1 non‐responsive disease have poor response rates (Aya et al, ; Bowyer et al, ; Jacobsoone‐Ulrich et al, ; Zimmer et al, ). We showed that PLX51107 profoundly reduced the growth of mouse melanomas in vivo that were non‐responsive to anti‐PD‐1 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Developing second‐line therapies is key as the treatment options for these patients are ineffective. For example, melanoma patients treated with anti‐CTLA‐4 as a second‐line therapy for anti‐PD‐1 non‐responsive disease have poor response rates (Aya et al, ; Bowyer et al, ; Jacobsoone‐Ulrich et al, ; Zimmer et al, ). We showed that PLX51107 profoundly reduced the growth of mouse melanomas in vivo that were non‐responsive to anti‐PD‐1 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We administrated ipilimumab to patients who showed disease progression while being treated with an anti‐PD‐1 antibody. In past reports, the objective response rates were 3.6–16% in advanced melanoma patients given an anti‐PD‐1 antibody followed by ipilimumab . However, ipilimumab therapy is reportedly used more frequently and produces more severe immune‐related adverse events (irAE) than nivolumab .…”
Section: Introductionmentioning
confidence: 99%
“…In our case, upon activation of antiTg and possibly anti-ACTH immunity with cross presentation of melanoma antigen, exacerbation of thyroiditis and deterioration of ACTH secretion might be seen. Bowyer et al reported that in 35% of patients with melanoma who received anti-CTLA-4 antibody after discontinuation of anti-PD-1 antibody, grade 3-4 irAEs were developed (16). They report clinical benefits of a sequential administration of nivolumab followed by ipilimumab in patients with advanced melanoma, albeit associated with a higher frequency of adverse events.…”
Section: Ariyasu Et Almentioning
confidence: 99%